Role of Endocrine-Disrupting Engineered Nanomaterials in the Pathogenesis of Type 2 Diabetes Mellitus - Priyam, Ayushi; Singh, Pushplata Prasad; Gehlout, Shweta (Frontiers in Endocrinology, 2018)
Nanotechnology has enabled the development of innovative technologies and products for several industrial sectors. Their unique physicochemical and size-dependent properties make the engineered nanomaterials (ENMs) superior for devising solutions for various research and development sectors, which are otherwise unachievable by their bulk forms. However, the remarkable advantages mediated by ENMs and their applications have also raised concerns regarding their possible toxicological impacts on human health. The actual issue stems from the absence of systematic data on ENM exposure-mediated health hazards. In this direction, a comprehensive exploration of the health-related consequences, especially with respect to endocrine disruption related metabolic disorders are largely lacking. The reasons for a rapid increase in diabetes and obesity in the modern world largely remain unclear and epidemiological studies indicate that the increased presence of endocrine disrupting chemicals (EDCs) in the environment may influence the incidence of metabolic diseases. Functional similarities, such as to mimic natural hormonal actions, have been observed between the endocrine-disrupting chemicals (EDCs) and ENMs, which supports the view that different types of NMs may be capable of altering the physiological activity of the endocrine system. Disruption of the endocrine system leads to hormonal imbalance, which may influence the development and pathogenesis of metabolic disorders, particularly type 2 diabetes mellitus (T2DM). Evidence from many in vitro, in vivo and epidemiological studies, suggest that ENMs generally exert deleterious effects on the molecular/hormonal pathways and the organ systems involved in the pathogenesis of T2DM. However, the available data from several such studies are not congruent, especially because of discrepancies in study design, and therefore needs to be carefully examined for drawing meaningful inferences. In this review, we discussed the outcomes of ENM exposure in correlation with the development of T2DM. In particular, the review focused on the following sub-topics: (1) an overview of the sources of human exposure to NMs; (2) systems involved in uptake of ENMs into human body; (3) endocrine disrupting engineered nano-materials (EDENMs) and mechanisms underlying the pathogenesis of T2DM; (4) evidence of role of EDENMs in the pathogenesis of T2DM from in vitro, in vivo and epidemiological studies; (5) conclusions and perspectives.